Research on the Application of Blockchain Technology in the Security Protection of Sensitive Data in Information Systems - Cao, Yun (Journal of Cyber Security and Mobility, 2025)
With the acceleration of informatization, the security of sensitive data in information systems has increasingly become the focus of global attention. Especially in the context of the widespread application of big data, cloud computing and other technologies, data leakage and privacy risks are becoming more and more serious. Traditional data protection methods can no longer effectively deal with complex network attacks and data leakage problems, and new technical means are urgently needed to improve data security. Blockchain technology shows strong data protection potential due to its characteristics of decentralization, non-tampering and traceability, and is gradually being applied to the protection of sensitive data in information systems. This paper analyzes the application of blockchain technology in data storage, transmission and access control, and discusses its effectiveness in improving data security. We selected the customer information system of a well-known financial institution as the research object, and used blockchain technology to encrypt, store and distribute management of sensitive data. The experimental results show that after the introduction of blockchain technology, the data leakage rate of the system has dropped by 78%, and at the same time, the response time of the system has increased by 22% compared with traditional data protection technology. In addition, the access control mechanism based on smart contracts significantly improves the transparency and traceability of data operations, effectively reducing unauthorized access. This article proves the effectiveness of blockchain technology in protecting sensitive data security in information systems through the analysis of practical cases.